The Influence of Talent Management and Knowledge Management on the Performance of Employees with Engagement Employees as an Intervening Variable in PT. Bank Sumut Head Office Medan - Napitupulu, Fernando; Siahaan, Elisabet; Harahap, R Hamdani (Formosa Journal of Science and Technology, 2024)
This study aims to analyze the influence of talent management and knowledge management on employee performance, with employee attachment as an intervening variable at PT Bank Sumut Medan Head Office. The study used a quantitative approach with an associative research design, involving 83 employees who were selected through the proportional random sampling technique. Data were collected using questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results of the study show that talent management and knowledge management have a significant positive influence on employee engagement. Employee attachment also has a significant positive effect on employee performance. In addition, employee attachment mediates the influence of talent management and knowledge management on employee performance. These findings confirm the importance of a holistic strategy in human resource management to improve performance. The implications of the research include the need for strategic talent management, the development of knowledge management infrastructure, and programs that support the work-life balance of employees. This research contributes to the academic literature in the field of human resource management and provides practical guidance for organizations in designing employee performance improvement strategies.